2006
DOI: 10.1007/s11267-005-9015-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization and Biodegradation of VOCs in Membrane Bioreactors (MBR)

Abstract: Volatilization and biodegradation are major competitive volatile organic compound (VOC) removal mechanisms in biological wastewater treatment process, which depend on compound specific properties and system design/operational parameters. In this study, a mathematical model was used to determine major removal pathways at various organic loading rates (OLR), solids residence time (SRT) and dissolved oxygen (DO) concentrations in a biological process for vinyl acetate. Model results showed that biological treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Similar result has been reported by Min and Ergas [37]. They reported that higher biodegradation of vinyl acetate reduced the volatilization loss to less than 0.59%, while treating synthetic wastewater containing VOC using an MBR at an OLR of 2.0 kg COD/m 3 days.…”
Section: Performance Evaluation Of Mbr With Asp As Pretreatment Systesupporting
confidence: 88%
“…Similar result has been reported by Min and Ergas [37]. They reported that higher biodegradation of vinyl acetate reduced the volatilization loss to less than 0.59%, while treating synthetic wastewater containing VOC using an MBR at an OLR of 2.0 kg COD/m 3 days.…”
Section: Performance Evaluation Of Mbr With Asp As Pretreatment Systesupporting
confidence: 88%
“…Min and Ergas [15] have developed a mathematical model for treatment of VOC-containing wastewaters in MBRs which is a modified version of the model developed for CASPs by Hsieh [4]. This model, together with limited experimental data obtained for treatment of vinyl acetate synthetic wastewater in a laboratory side-stream MBR, predicts that unlike CASP processes, in MBRs, with increase in OLR (e.g.…”
Section: Cod and Styrene Removal Performance Of The Mbr Systemmentioning
confidence: 99%
“…For this reason, the air rates, reportedly used in MBR processes, are usually higher than those of CASPs [13,14]. However, according to the CASP model developed by Hsieh [4] and the MBR model developed by Min and Ergas [15], increase in air rate can lead to significant increase in the removal rate of VOCs by stripping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, a model was developed for the treatment of mixed gas streams of VOCs in biofilters. Kyungnan et al [68] utilized mathematical models to determine the results of vinyl acetate removal at different organic loading rates, solid residence times, and dissolved oxygen concentrations. Currently, the method of predicting and evaluating bioreactor operating parameters and effectiveness by constructing models needs further exploration and investigation.…”
Section: Analysis Of Research Trendsmentioning
confidence: 99%